Decompressive craniotomy for severe traumatic brain injury: Our experience and review of literature - Sharma, Krishna (Nepal Journal of Neuroscience, 2024)
Introduction: Severe traumatic brain injury (TBI) is the most devastating injury affecting physical, mental, social and financial health of an individual and a society. The research, understanding and management of TBI is mainly focussed towards the secondary effects of the traumatic brain injury. Maintaining intracranial pressure within reasonable bounds is essential for successful TBI therapy, as an uncontrolled intracranial pressure (ICP) plays a major role in determining the course and prognosis of the injury. In general, ICP can be managed medically and/or surgically. In this article, we discuss our experience, the most recent understanding, and a method for managing ICP in traumatic brain injury. Material and Methods: This study comprised 350 patients with moderate to severe traumatic brain injury (TBI) who were treated by a single neurosurgeon at several institutions between 2005 and 2020. 76.6% (268) of the patients were men, and 64% (224) of the patients were under 60 years old. The most common mode of injury was road traffic accident followed by fall from height. The study excluded those patients with brain stem injuries, bilateral non-reacting pupils, and concomitant significant injuries in other body parts. All were first treated medically with appropriate resuscitation, hyper-osmolar therapy (mannitol, 3% saline), hyperventilation, and barbiturate coma as per the response and requirement. Surgical intervention was used for patients who did not respond to medical management. In addition, decompressive craniectomy (DC) was primarily performed on those whose GCS was less than 5 and who had reacting pupils, upon presentation. Results: Out of the 350 patients, 53.2% (186) had moderate TBI and 46.8% (164) had severe TBI. Due to failure of medical management, 30.5% (54) of moderate and 69.5% (123) of severe TBI underwent decompressive craniectomy in the form of bifrontal craniectomy in 18% (32), unilateral fronto-temporo-parietal craniectomy (hemicraniectomy) in 64% (113) , bilateral hemicraniectomy in 6% (11) and 12% (21) underwent limited fronto-temporo-parietal craniectomy. Decompressive craniectomy was not performed for posterior fossa. The data on outcome is very poor, inadequate and unreliable due to bad follow up. 5 years Follow up could be obtained only of 127 out of 350 (36%) patients and majority of these 69% (88) were moderately or severely disabled. Of those operated ones, only 27% (48) agreed for cranioplasty. 17% (30) had to undergo VP shunt for hydrocephalus. The group with severe traumatic brain injury (TBI) accounted for the majority of deaths (17%), with respiratory tract infections being the primary cause. Conclusion: Decompressive craniectomy is the sole option in medically refractory cases of traumatic intracranial hypertension, who continue to deteriorate clinically. Nevertheless, the benefit falls short of expectations, particularly with regard to functional recovery. However prompt and appropriate decompression in appropriately indicated patients has withstood the test of time and remains a widely accepted attempt at life saving for moderate-to-severe traumatic brain injury.